ANALISIS KONSTRUKTIVISME TERHADAP KESULITAN BELAJAR SISWA DALAM MEMAHAMI MATERI - Rahma Pramudianti Pratama; M Mamduh Winangun (JURNAL ILMIAH NUSANTARA, 2026)
The main problem in the learning process is the inability of students to understand what is being taught, due to a lack of adequate conceptual skills, poor critical thinking abilities, and an insufficient correlation between the concepts taught and real-world situations. The above indicates that there is still room for improvement in the current process, given that most activities are focused on the teacher as the source of information. This paper offers an extensive analysis of the underlying causes behind the learning challenges faced by students as well as potential solutions based on the principles of constructivist learning theory. The method used in this research is secondary data analysis through a literature review. The theory underlying this work is called constructivism, which views learning as a highly participatory experience in which learners create their own knowledge by connecting it to prior experiences. It turns out that the above learning obstacles arise from inadequate student participation, poor social interaction among peers, and the poor application of learning approaches. Several empirical studies show that the above learning problems can be overcome through the application of constructivism.